KELAYAKAN AWETAN BASAHSEBAGAI MEDIA PEMBELAJARAN SUBMATERI PROTISTA MIRIP TUMBUHAN - Ananta, Evi Dian; Syamswisna, Syamswisna; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to know the feasibility of wet-preserved media in the studying sub-material of plant-like protists (algae) for Senior High School tenth.The form of research was quantitative descriptive methods.Validation sheet was used as the instrument of research. Each statemen item is divided into categories Very Good is worth 4, Good is worth 3, Less Good is worth 2, and Not Good is worth 1. Based on the validator's assessment, the wet-preserved media wasdeclared valid with CVR and CVI values of 0,99, so that it was suitable tobe used as a learning mediain studying sub-material of plant-like protists (algae). The macroalgae wet-preserved media were validated by five validators consisting of three high school Biology teachers and two Biology education lecturers from FKIP Untan. Based on the validator's assessment, the wet-preserved media was declared valid with CVR and CVI values of 0,99 (valid), so that it was feasible to be used as a learning media in studying sub-material of plant-like protists (algae).Â Keywords: wet-preserved, learning media, plant-likeprotists (algae)Â